Asymptomatic and Unrecognized Cement Pulmonary Embolism Commonly Occurs with Vertebroplasty - Luetmer, M.T. (AJNR Am J Neuroradiol, 2011)
BACKGROUND AND PURPOSE: Cement PE represents a potentially serious complication following vertebroplasty. To determine the frequency and extent of cement PE during percutaneous vertebroplasty, we performed a retrospective review of chest CT scans obtained in patients who had previously undergone ≥1 vertebroplasty procedure. MATERIALS AND METHODS: After approval by our local institutional review board, we retrospectively evaluated 244 patients who had undergone vertebroplasty at 465 levels and subsequently underwent chest CT. A thoracic radiologist evaluated the presence, number, size, and location of discrete cement PEs. We catalogued the following data: age, sex, number of treated vertebrae, cement volume per vertebra, operator, presence of cement leakage noted by the operator during the procedure, and clinical presentation at postvertebroplasty CT. RESULTS: At least 1 cement PE was detected in 23 (9.4%; 95% CI, 6%–13%) of 244 patients; 1 patient was symptomatic from a cement PE. The mean number of discrete cement PEs was 3.2 ± 3.4 (median, 2; range, 1–12). There was no correlation among the total number of treatment sessions, number of levels treated per session, cement volume per level, operator, or time between vertebroplasty and chest CT in the detection of cement PE. Those with PE were significantly younger (P = .0229) and had significantly more total levels treated (P = .0260). Cement PE was recognized by the operator during the vertebroplasty in 2 (8.7%) of 23 patients found to have it on CT. CONCLUSIONS: Small asymptomatic cement PEs are common during vertebroplasty and usually are not recognized by the operator during the procedure.